2022
DOI: 10.3389/fimmu.2022.841290
|View full text |Cite|
|
Sign up to set email alerts
|

Adenosine A2A Receptor Suppressed Astrocyte-Mediated Inflammation Through the Inhibition of STAT3/YKL-40 Axis in Mice With Chronic Cerebral Hypoperfusion-induced White Matter Lesions

Abstract: White matter lesions are an important pathological manifestation of cerebral small vessel disease, with inflammation playing a pivotal role in their development. The adenosine A2a receptor (ADORA2A) is known to inhibit the inflammation mediated by microglia, but its effect on astrocytes is unknown. Additionally, although the level of YKL-40 (expressed mainly in astrocytes) has been shown to be elevated in the model of white matter lesions induced by chronic cerebral hypoperfusion, the specific regulatory mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Thirdly, as an endothelial-related inflammatory mediator, YKL-40 could activate endothelial cells to induce intercellular adhesion molecule-1 expression, 37 which would further recruit leukocytes and release pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β and interferon-γ, leading to endothelial dysfunction and BBB disruption. 38 , 39 Additionally, according to the latest research, 30 YKL-40 expression in astrocytes was elevated in white matter lesions caused by chronic hypoxia, and downregulating the expression of YKL-40 significantly alleviate white matter injury, suggesting that YKL-40 is implicated in the process of white matter injury. Taken together, the mechanisms mentioned above might be significant contributors to YKL-40 with PV-WMH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thirdly, as an endothelial-related inflammatory mediator, YKL-40 could activate endothelial cells to induce intercellular adhesion molecule-1 expression, 37 which would further recruit leukocytes and release pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β and interferon-γ, leading to endothelial dysfunction and BBB disruption. 38 , 39 Additionally, according to the latest research, 30 YKL-40 expression in astrocytes was elevated in white matter lesions caused by chronic hypoxia, and downregulating the expression of YKL-40 significantly alleviate white matter injury, suggesting that YKL-40 is implicated in the process of white matter injury. Taken together, the mechanisms mentioned above might be significant contributors to YKL-40 with PV-WMH.…”
Section: Discussionmentioning
confidence: 98%
“…In a mouse model of WMH induced by chronic cerebral hypoperfusion, the expression of YKL-40 was shown to be elevated. 30 A recently published community-based study with 960 Chinese stroke-free participants observed a significant association between elevated levels of endothelial-related inflammatory biomarkers including YKL-40 and increased WMH volume. 9 In another study with 42 sporadic CSVD patients, CSF levels of YKL-40 were positively correlated with the WMH load.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the activation of adenosine A2A receptor could inhibit the expression of YKL-40 and thereby alleviate white matter injury in cerebral small vessel disease [24]. Furthermore, Bonneh-Barkay et al have reported that absence of YKL-40 in mice resulted in more pronounced neuroinflammation and gliosis, suggesting a potential role of YKL-40 as therapeutic candidate for modulating neuroinflammation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Its regulation has been shown to affect cognition in experimental models (Raber et al, 2014; Sun et al, 2020), and may activate Erk and Akt pathways and Wnt signalling (Geng et al, 2018), pathways associated with cognitive impairment (Albert-Gascó et al, 2020; Oliva et al, 2013; Shu et al, 2013). Of relevance, activation of the adenosine A2a receptor (ADORA2A), may decrease YKL-40 expression in astrocytes and alleviate neuroinflammation and white matter injury (Yuan et al, 2022). Dysregulation of ADORA2A in astrocytes has been shown to disrupt glutamate homeostasis leading to cognitive impairment, and in a SZ subgroup, reduced striatal ADORA2A levels is accompanied by an altered psychomotor phenotype (Matos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%